THE IMPACT OF MODERN ENGLISH NOVELISM TO DEVELOPMENT OF CREATIVE METHODS IN UZBEK LITERATURE: THE IMPACT OF MODERN ENGLISH NOVELISM TO DEVELOPMENT OF CREATIVE METHODS IN UZBEK LITERATURE - Abdujabbarova, Kamola (Журнал иностранных языков и лингвистики, 2023)
This article presents research on the impact of modern English novelism to development of creative methods in Uzbek literature.